2017
DOI: 10.1139/apnm-2016-0274
|View full text |Cite
|
Sign up to set email alerts
|

Association between Maternal Dietary Inflammatory Index (DII) and abortion in Iranian women and validation of DII with serum concentration of inflammatory factors: case-control study

Abstract: Background: Previous studies have shown that some dietary components may be implicated in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 48 publications
2
65
0
Order By: Relevance
“…Cross-sectional analysis from Polish-Norwegian Study (PONS) and National Health and Nutrition Examination Survey (NHANES) presented a DII mean of 0.93 ± 1.44 [47] and 0.87 ± 1.08 [54], respectively. In a case control study with women that aborted, the DII was 1.51± 0.63 in cases and 1.22± 0.63 in controls [55]. Based on that, this may have contributed to the lack of association with some anthropometric and biochemical markers related to cardiometabolic risk in our study.…”
Section: Discussionmentioning
confidence: 56%
“…Cross-sectional analysis from Polish-Norwegian Study (PONS) and National Health and Nutrition Examination Survey (NHANES) presented a DII mean of 0.93 ± 1.44 [47] and 0.87 ± 1.08 [54], respectively. In a case control study with women that aborted, the DII was 1.51± 0.63 in cases and 1.22± 0.63 in controls [55]. Based on that, this may have contributed to the lack of association with some anthropometric and biochemical markers related to cardiometabolic risk in our study.…”
Section: Discussionmentioning
confidence: 56%
“…found that a high BMI prior to pregnancy is associated with a pro‐inflammatory diet and high levels of CRP during pregnancy . In order to evaluate the inflammatory potential of diet in terms of the risk of recurrent miscarriage, Vahid et al . examined the relationship between dietary inflammatory index scores and risk of miscarriage among women with a history of RPL.…”
Section: Discussionmentioning
confidence: 99%
“…examined the relationship between dietary inflammatory index scores and risk of miscarriage among women with a history of RPL. They concluded that women who consumed a more pro‐inflammatory diet had a higher risk of miscarriage compared with women who consumed a more anti‐inflammatory diet …”
Section: Discussionmentioning
confidence: 99%
“…A literature-derived, population-based dietary inflammatory index (DII) was developed to assess the inflammatory potential of an individual's diet (22). DII has previously been shown to be associated with various inflammatory markers in different populations (2328) including among Iranians (29, 30). With respect to health outcomes, DII was significantly associated with different health outcomes ranging from cardiovascular diseases (3133), cancer (3437), overall and disease-specific mortality (3842) to various mental health disorders (43–47).…”
Section: Introductionmentioning
confidence: 99%